1979
DOI: 10.1007/bf01869294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bicarbonate on fluid and electrolyte transport by the guinea pig gallbladder: A bicarbonate-chloride exchange

Abstract: Fluid transport and net fluxes of Na, K, Cl and HCO3 by guinea pig gallbladder were investigated in vitro. A perfused gallbladder preparation was devised to simultaneously study unidirectional fluxes of 22Na and 36Cl. The net Cl flux exceeded the net Na flux during fluid absorption in the presence of HCO3. This Cl excess was counterbalanced by a net HCO3 secretion: a HCO3-Cl exchange. PGE1 reversed the direction of fluid transport and abolished the net Cl flux. The magnitude of the HCO3 secretion remained unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…It is only comparatively recently, however, that this and related anion exchanges have been studied in detail, not only in red blood cells (Deuticke, 1972;Cousin & Motais, 1976;Lambert & Lowe, 1978;Cabantchik, Knauf & Rothstein, 1978; Wieth, 1979) but also in excitable tissues (Thomas, 1977;Vaughan-Jones, 1979) and a wide variety of transporting epithelia including the gastric mucosa (Sanders, O'Callaghan, Butler & Rehm, 1972), turtle urinary bladder (Leslie, Schwartz & Steinmetz, 1973), the collecting duct of the exocrine pancreas (Swanson & Solomon, 1975), colon (Frizzell, Koch & Schultz, 1976) and gall-bladder (Heintze, Petersen, Olles, Saverymuttu & Wood, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…It is only comparatively recently, however, that this and related anion exchanges have been studied in detail, not only in red blood cells (Deuticke, 1972;Cousin & Motais, 1976;Lambert & Lowe, 1978;Cabantchik, Knauf & Rothstein, 1978; Wieth, 1979) but also in excitable tissues (Thomas, 1977;Vaughan-Jones, 1979) and a wide variety of transporting epithelia including the gastric mucosa (Sanders, O'Callaghan, Butler & Rehm, 1972), turtle urinary bladder (Leslie, Schwartz & Steinmetz, 1973), the collecting duct of the exocrine pancreas (Swanson & Solomon, 1975), colon (Frizzell, Koch & Schultz, 1976) and gall-bladder (Heintze, Petersen, Olles, Saverymuttu & Wood, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In the guinea-pig HC03-both enhances Na+ salt absorption and elicits a HC0 3-secretion (Heintze et al 1979). In spite of these two overlapping effects, K+ activity largely and significantly decreases (by 44 4 + 4-3 mm) and Na+ activity increases (by 330 + 42 mM), a result which suggests that HCO3-also increases Na+ entry at the apical membrane in this species, as in the rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…and Petersen, Wood, Schulze & Heintze (1981) have clearly shown that the latter hypothesis is more likely and also extended their study to guinea-pig gall-bladder. Bicarbonate effects are more complex in this species, since an HCO3-secretion is also elicited in the presence of the anion (Herman, Wilson & Kazyak, 1958;Heintze, Petersen, Ollen, Saverymuttu & Wood, 1979). We have demonstrated recently that the apical membrane exhibits an anion conductance in the guinea-pig, but not in the rabbit (Cremaschi & Meyer, 1982), so that a relationship might exist between HCO3-secretion and such a conductance, following the current models on anion secretion (Frizzell, Field & Schultz, 1979).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The efflux of radiolabelled calcium was markedly enhanced by prelabelling in the presence of theophylline and excess K+, as compared to prelabelling in the presence of excess K+ alone. The movements of chloride and bicarbonate ions across a variety of tissues have been shown to be inhibited by SITS (4-acetamido-4-isothiocyanatostilbene 2,2-disulphonic acid; see Heintze, Olles, Petersen & Wood, 1978). Although SITS inhibits net fluid flux in the proximal convoluted tubule of rat kidney (Green & Greenwood, 1978), its effect on tubular anion fluxes has not been reported.…”
Section: Pmentioning
confidence: 99%